Antioxidant activity and possible bioactive components in hydrophilic and lipophilic fractions from the seaweed Halimeda incrassata - Novoa,Alexis Vidal (2011)
Hydrophilic and lipophilic fractions, obtained from the marine algae Halimeda incrassata (J.Ellis) J.V.Lamouroux, Halimedaceae, were studied by using the ²-carotene-linoleate assay system. In case of hydrophilic fractions, the total phenolic compounds were quantified and two of their components were identified as salicylic and ferulic acids. From the lipophilic fraction, fatty acid composition was studied. The highest antioxidant activities values were found on the polar fractions containing phenolic acids. The total phenolics content on the hydrophilic fractions was 255 μg of gallic acid equivalents/g of fresh seaweed. To further characterize H. incrassata chemical composition, the total lipid content was quantified (7.4 mg per gram of dried algae) as well as the saturated and unsaturated fatty acids ratio (1:1.46). In summary, this paper adds more convincing evidences in support of the antioxidant abilities of the lyophilized aqueous extract of Halimeda incrassata and it also relates this bioactivity, for the first time, with particular phenolic components of the extract. Altogether, these results represent another step towards the use of this natural product as drug candidates.